Antibacterial and Preservative Potential of Eugenol and Isoeugenol in Cosmetics: A Natural Solution for Product Stability - Anna Fajdek-Bieda; Joanna Pawlińska; Agnieszka Wróblewska; Wojciech Żwierełło; Agnieszka Łuś; Adam Klimowicz (Applied Sciences, 2025)
Eugenol (EU) and isoeugenol (IZO-EU) are naturally occurring compounds known for their strong antibacterial properties, which makes them ideal candidates for application as preservatives in cosmetic products. Primarily derived from clove oil, EU demonstrates potent antibacterial effects against a wide range of microorganisms, including Gram-positive and Gram-negative bacteria, as well as yeast-like fungi such as Candida albicans. Their antibacterial action is mainly connected with their ability to disrupt microbial cell membranes and inhibit key enzymatic processes. IZO-EU, a structural isomer of EU, also shows significant activity against various pathogens. In these studies, the effectiveness of EU and IZO-EU as preservatives in cosmetic formulations was tested. The antibacterial activity tests, using the disk diffusion method, assessed their effectiveness against Enterococcus faecalis, Staphylococcus aureus (Gram-positive), Escherichia coli, Pseudomonas aeruginosa (Gram-negative), and Candida albicans. Creams containing the different concentrations of EU and IZO-EU (0.5%, 1.5%, 2.5%) were tested for microbiological purity, texture, consistency, and stability over a defined storage period and under controlled conditions (temperature, humidity, and light exposure). Microbiological purity was assessed through the standard culture methods, while the texture and consistency were evaluated using rheological measurements and sensory analysis. The obtained results demonstrated that both compounds effectively preserved the creams, maintaining the microbiological purity without significantly altering the texture, consistency, or stability throughout the storage period. Additionally, EU and IZO-EU not only enhanced the antibacterial protection of the formulations but also contributed to the pleasant fragrance. Furthermore, preliminary studies were conducted on their anticancer properties using the LoVo (colon cancer) and U87MG (glioma) cell lines. These studies revealed the hormetic effects at the low concentrations and cytotoxicity at the higher doses, suggesting that EU and IZO-EU may have therapeutic potential beyond cosmetic applications. These studies support the application of EU and IZO-EU as natural, multifunctional ingredients in cosmetics, offering both preservative and sensory benefits while meeting the growing consumer demand for natural and sustainable solutions in the beauty industry.